2010
DOI: 10.1007/s12072-010-9170-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surveillance for hepatocellular carcinoma on tumor staging and treatment decisions in Egyptian patients

Abstract: Purpose Egyptian hepatocellular carcinoma (HCC) patients present at advanced stages. We aimed to study the influence of surveillance versus non-surveillance on HCC staging and the potential therapeutic options. Methods A retrospective study to evaluate the effect of surveillance on early detection of HCC among cirrhotic patients from 2003 to 2008. Patients examined every 6 months using ultrasound and a-fetoprotein (a-FP) (group A) and those diagnosed with those that present for the first time symptomatically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…But the frequency of elevated AFP did not differ with regards to MELD score or cirrhotic disease [36] . But there was significant positive correlation between AFP and CLIP, Tokyo, and VISUM staging system among HCC cases, these were in agreement with El-Shenawy et al [29] and El-Zayadi et al [37] who reported that there was significant positive correlation between AFP and CLIP staging systems.…”
Section: Discussionsupporting
confidence: 89%
“…But the frequency of elevated AFP did not differ with regards to MELD score or cirrhotic disease [36] . But there was significant positive correlation between AFP and CLIP, Tokyo, and VISUM staging system among HCC cases, these were in agreement with El-Shenawy et al [29] and El-Zayadi et al [37] who reported that there was significant positive correlation between AFP and CLIP staging systems.…”
Section: Discussionsupporting
confidence: 89%
“…Discussion:-HCC is the most common malignancy in Egypt, where there is the high prevalence of HCV infection all over the world. In Egypt, about 14% of the population has chronic HCV infection [17]. The delayed diagnosis of HCC leads to poor response to treatment.…”
Section: Results:-mentioning
confidence: 99%
“…Therefore, in the current study, we investigated the survival outcome of LC patients who received the surveillance program from the time it was implemented in South Korea. The mortality risk of patients who underwent the surveillance pro- 20 and had a better overall survival than those without surveillance. 18,[20][21][22] The time of survival was calculated from the point of HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality risk of patients who underwent the surveillance pro- 20 and had a better overall survival than those without surveillance. 18,[20][21][22] The time of survival was calculated from the point of HCC diagnosis. Data were censored at the date of death or last day of follow-up.…”
Section: Discussionmentioning
confidence: 99%